Bluetooth Low Energy: An implementation of the proximity profile and a feasibility analysis of key fob applications - Högfeldt, Joachim; Karlsson, Kristoffer (My University, 2013)
The Bluetooth Low Energy technology was introduced as part of the Bluetooth 4.0 specification in 2010, aiming to reduce the power consumption and cost of embedding wireless communication into electronic devices. Bluetooth Low Energy enables new application areas in addition to those already offered by classic Bluetooth technology, such as sensor networks, body monitors and smart keys. This thesis explores the possibility of using Bluetooth Low Energy for smart key applications, by implementing the Proximity profile and presenting a theoretical feasibility analysis of using such implementations. It is concluded that Bluetooth Low Energy offers sufficient security for using it as the wireless technology in smart key applications, and the Proximity profile is deemed to be a suitable option. Future studies should aim to develop a practical example and a protocol of how to use Bluetooth Low Energy and, e.g., the Proximity profile for smart key applications. In addition, the possibility of devising a standard based on this technology should be investigated.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology